Sustainable Strategies for Crystalline Solar Cell Recycling: A Review on Recycling Techniques, Companies, and Environmental Impact Analysis - Akhter M.; Al Mansur A.; Islam M.I.; Lipu M.S.H.; Karim T.F.; Abdolrasol M.G.M.; Alghamdi T.A.H. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Solar PV is gaining increasing importance in the worldwide energy industry. Consequently, the global expansion of crystalline photovoltaic power plants has resulted in a rise in PV waste generation. However, disposing of PV waste is challenging and can pose harmful chemical effects on the environment. Therefore, developing technologies for recycling crystalline silicon solar modules is imperative to improve process efficiency, economics, recovery, and recycling rates. This review offers a comprehensive analysis of PV waste management, specifically focusing on crystalline solar cell recycling. The classification of PV recycling companies based on various components, including solar panels, PV glass, aluminum frames, silicon solar cells, junction boxes, plastic, back sheets, and cables, is explored. Additionally, the survey includes an in-depth literature review concentrating on chemical treatment for crystalline solar cell recycling. Furthermore, this study provides constructive suggestions for PV power plants on how to promote solar cell recycling at the end of their life cycles, thereby reducing their environmental impact. Moreover, the techno-economic and environmental dimensions of solar cell recycling techniques are investigated in detail. Overall, this review offers valuable insights into the challenges and opportunities associated with crystalline solar cell recycling, emphasizing the importance of economically feasible and environmentally sustainable PV waste management solutions in the constantly evolving solar energy market. ? 2024 by the authors.